Aplica????o e aceitabilidade da farinha da casca do maracuj?? amarelo (Passiflora Edulis) na alimenta????o de um grupo de idosos - Oliveira, Danielle Karine Barbosa (2016)
Aging is defined as a complex process, which can undergo several changes as a result of the genetic and environmental factors, characterized by changes in morphological and physiological functions at all levels in the body. Among the environmental factors, diet plays an important role in the degenerative processes that are related to senescence, resulting in a progressive decline in physiological capacity and increased susceptibility and vulnerability to diseases typical of aging, such as chronic non communicable diseases. Much of the incidence of these diseases is associated with poor habits of living and eating people. As a result, they may experience increased blood pressure, overweight, obesity, hyperglycemia and hyperlipidemia. The use of stored natural foods in regular diet of these individuals as dietary fiber, found especially in legumes and fruits, has proved to be an alternative in reducing the risk factors for these diseases. Among these foods highlights the species Passiflora edulis. The use of flour from the bark of this species, also known as passion fruit as a food ingredient, is a great economical option for the use of this byproduct, considering that has several health benefits such as the ability to reduce cholesterol and blood glucose levels in the organism. Allied to this, various research has developed preparations with the use of the flour of the yellow passion fruit peel, making this product sensuously accepted among consumers. Allied to this, various research has developed preparations with the use of the flour of the yellow passion fruit peel, making this product sensuously accepted among consumers. Objectives: This study aimed to evaluate a group of CCI / UCB elderly, the intake of fiber and propose two savory preparations containing flour from the bark of yellow passion fruit as a functional food ingredient and verify the acceptability of the preparations. Methods: First, we analyzed the daily intake of fiber from goers elderly Elderly Community Centre (JRC) of the Catholic University of Brasilia (UCB) through the record 24 (24HR). For the choice of test-preparations were used data from history and 24hR the elderly. The foods selected for insertion of the fiber were the eggplant pie and tapioca. Sensory analysis was performed by 34 untrained panelists, and involved two types of affective tests: assessment of overall impression, using the nominal hedonic scale of nine points, and evaluation of intention to use seven points. For the evaluation of 24HR and preparations, we used the Virtual Nutri Plus?? software. Results: It was observed that all of the sample men ingest an average of fibers 12.71 ?? 5,62g / day, 57.64% below the recommended (30g) and only two women (6.7%) reached the recommendation daily total fiber (21g). The rest of the female sample ingests on average 11.86 ?? 4,84g / day, 43.52% below the recommended fiber value. The inclusion of flour peel of Passiflora edulis (FCPE) in preparing the eggplant pie and tapioca showed acceptance, averaging 8.06 ?? 1.39 and 8.41 ?? 0.99, respectively. Attitude scale tests confirmed that most always consume tapioca (64.7%) and eggplant cake (61.8%). The results of the acceptability index showed the feasibility of addition of passion fruit flour in usual preparations of the elderly with 89.55% for eggplant pie and 93.44% for tapioca. All preparations after insertion of FCP and obtained 3g fiber / 100g of prepared foods, which characterizes a food source of fiber.